Kinerja Kelompok Tani dalam Peningkatan Produksi Jagung (Zea mays L.) di Lahan Kering, Desa Labuhan Sangoro Kecamatan Maronge Kabupaten Sumbawa - Nurwahidah, Siti; Wijayanti, Nila; Wartiningsih, Alia; Hartono, Yadi; Wahyuni, Sri (AGRIFITIA : Journal of Agribusiness Plantation, 2023)
This research aims to analyze the performance of farmer groups in increasing corn production in dry land, Labuhan Sangoro Village, Maronge District, Sumbawa Regency. The farmer groups sampled were 6 farmer groups from corn farmer groups in dry land which were determined using purposive sampling, data analysis techniques using a Likert scale with five indicators. The research results show that as many as 3 indicators perform well, namely indicators (1) planning activities, (2) carrying out activities and complying with agreements with other parties, and (3) application of technology and use of information; Meanwhile, 2 indicators performed quite well, namely indicators: (1) capital fertilization and (2) institutional relations between farmer groups and gapoktan. Overall, the performance of farmer groups in Sangoro Village, Maronge District, performed well with an average score of 2.88.